PEMASARAN PERPUSTAKAAN DI ERA DIGITAL NATIVES - Dian Wulandari (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
Library marketing plays an important role in increasing the number of visitors, increasing the utilization of facilities and library collections and improving the image of libraries and their main institution. In this era of digital natives, libraries need to apply the marketing mix strategy -as is done in corporate marketing- so that library marketing can run as a whole -not just a promotional effort- certainly by observing the characteristics of the present generation that has different needs for library from the previous generation in the collections, service facilities and library rooms. The library marketing cycle is necessary for the marketing program to have a clear plan; ensuring that library work programs run ontinuously, run as target and are clearly measured. Thus the purposes of library marketing can be achieved.